2018
DOI: 10.2196/publichealth.9307
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Lower Respiratory Tract Infections and Atopic Conditions in Boys and Young Male Adults: Royal College of General Practitioners Research and Surveillance Centre Annual Report 2015-2016

Abstract: BackgroundThe Royal College of General Practitioners Research and Surveillance Centre comprises more than 150 general practices, with a combined population of more than 1.5 million, contributing to UK and European public health surveillance and research.ObjectiveThe aim of this paper was to report gender differences in the presentation of infectious and respiratory conditions in children and young adults.MethodsDisease incidence data were used to test the hypothesis that boys up to puberty present more with lo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 38 publications
4
14
0
Order By: Relevance
“…The factors associated with increased household incidence may provide some insights into where public health interventions might best be directed. Gender differences are hard to explain, but we have reported, by way of contrast, greater presentation of boys with respiratory infections and atopic conditions to primary care [27]. We are unclear as to whether this is related to disease frequency or propensity to consult, of if due to another cause of gender bias.…”
Section: Implications Of the Findingsmentioning
confidence: 74%
See 1 more Smart Citation
“…The factors associated with increased household incidence may provide some insights into where public health interventions might best be directed. Gender differences are hard to explain, but we have reported, by way of contrast, greater presentation of boys with respiratory infections and atopic conditions to primary care [27]. We are unclear as to whether this is related to disease frequency or propensity to consult, of if due to another cause of gender bias.…”
Section: Implications Of the Findingsmentioning
confidence: 74%
“…We can't differentiate what might be increased propensity to consult, or to attend with an unwell child under 5-years than an older adult, something demonstrated in rotavirus infection [43]. However, the propensity to consult is also impacted by gender, ethnicity or socioeconomic status [27]. However, the need to consult is also driven by the health of the child and our pattern of attendance appears to be similar to that of admission to hospital with AGE [44,45].…”
Section: Limitations Of the Studymentioning
confidence: 88%
“…Previous studies have reported that male children have higher rates of respiratory illnesses. 16 17 36 Lusignan et al, 36 observed a higher incidence of family doctors contacts in males <15 years due to LRTI compared with females of the same age, with the largest gender difference in the youngest age group (<1 year). This study also noted a higher contact rate in males <15 years due to asthma.…”
Section: Main Findings and Comparison To Literaturementioning
confidence: 99%
“…Primary care surveillance systems such as the Royal College of General Practitioners (RCGP) Research and Surveillance Centre (RSC) are considered the 'gold standard' for primary care surveillance. [2][3][4] Respiratory infections cause an annual burden on health services, particularly during the winter. 5 General practitioner (GP) consultations, emergency department attendances, hos-pital admissions and deaths can all increase during the winter season, placing added pressures on di erent aspects of the health service.…”
Section: Introductionmentioning
confidence: 99%